Integrasi Green Accounting Dalam Strategi Pemasaran Membentuk Citra Merek Sustainability Pada Konsumen Gen-Z - Hamizar, Arizal; Karnudu, Fitria; Yaman, Afdhal; Pellupessy, Fatmah Watti; Malawat, Fadli Fendi (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2024)
This research aims to explore how Generation Z responds to green accounting practices and its impact on brand image, as well as to formulate appropriate marketing strategies based on these findings. The research method employed is qualitative with a phenomenological approach. Data were collected through in-depth interviews, and data analysis was conducted using a thematic approach to identify thematic patterns emerging from interviews and observations. The results of the study indicate that Generation Z responds positively to green accounting practices, considering it a key differentiator in brand selection. The implementation of green accounting has a positive impact on brand image, with respondents perceiving companies adopting green accounting practices as pioneers and leaders in conducting business responsibly. Subsequently, based on the research findings, formulating marketing strategies that consider sustainability values becomes crucial in meeting the preferences and expectations of Generation Z.